Neuropsychiatric Manifestations of Antiphospholipid Syndrome—A Narrative Review - Yik Long Man; Giovanni Sanna (Brain Sciences, 2022)
Antiphospholipid syndrome (APS) is a common autoimmune pro-thrombotic condition characterised by thrombosis and pregnancy morbidity. There are a broad range of neuropsychiatric manifestations associated with APS, from focal symptoms to more global dysfunction. Patients commonly present with transient ischaemic attacks and ischaemic strokes, with identifiable lesions on brain imaging. However, the underlying pathogenesis remains uncertain in other manifestations, such as cognitive dysfunction, seizures, headache and chorea. The aim is to provide a comprehensive review of the various neuropsychiatric manifestations associated with APS. A detailed literature search was applied to PubMed, including citations from 1983 to December 2021.